Google Sites-Based Project-Based Learning (PJBL) Integration Model as a Structured Digital Portfolio - Desy Irsalina Savitri; Mety Toding Bua; Weldi Nugroho Detagory; Nindya Adiasti; Oriza Zativalen (JURNAL ASIMILASI PENDIDIKAN, 2026)
The novelty of this research lies in the integration of technology applied to the project-based learning process through structured documentation that supports digitalization. The development of a Google Sites-based PjBL (Project-Based Learning) model integrated with a phased digital portfolio structure (planning–implementation–reflection–evaluation), which has not been systematically studied among PGSD (Primary School Teacher Education) students taking the Developmental Psychology of Learners course. Students can learn from anywhere, complete assignments, and lecturers can document all student assignments neatly stored as digital documents. The article uses a mixed method combining quantitative and qualitative descriptive approaches: the quantitative aspect is measured from student response questionnaires after using the application, while the qualitative aspect comes from in-depth interviews and documentation of individual portfolio reports neatly organized for each meeting. This learning approach combines technological sophistication with efforts to reduce paper usage in the learning process. The researcher utilizes technology by integrating Google Sites. The results of this research can be seen from the questionnaire distributed to 35 students regarding: 1) The suitability of interactive multimedia learning with the learning theme, 2) Interactive Google Sites multimedia increases my enthusiasm for learning, 3) The multimedia's capability as a tool to understand and remember learning materials, 4) Challenges in using Google Sites and uploading portfolio assignments. In conclusion, the data results show that the portfolios are neatly stored in the Google Sites web as an integration of structured digital documents, serving as a tool in the distance learning process that also challenges students' critical thinking.